Relationship between RHB bond fund and macroeconomic variables / Hanif Hashim - Hashim, Hanif (Faculty of Business and Management, 2010)
The research studies on the relationship of economic variables with bond price. The scope of the study only focuses on the price movement of RHB bond fund price as a result of the changing in the money supply, inflation and consumer price index. The objective of the study is to determine the relationship between the economic variables with the price movement of RHB bond fund. There are three economic variables which are chosen in this study which is money supply, inflation rate and consumer price index. The data period cover from January 2005 until December 2009. The data retrieved from the DataStream. The Autoregressive (AR) Model is used to investigate the relationship between the economic variables with RHB bond fund price.